Perlindungan Anak di Era Digital: Analisis Yuridis terhadap Landasan Hukum dan Implikasinya pada Strategi Pembelajaran Pendidikan Agama Kristen Berbasis Teknologi - Mulianto Mulianto; Ferry Yeferson Tulle; Christopher Cahyadi; Djuwansah Suhendro; Juanda Julianus; Ferry Setiawan (Sekolah Tinggi Teologia Kerusso Indonesia, 2025)
The rapid development of digital technology in the past decade has transformed Christian Religious Education (PAK) through synchronous–asynchronous models, Learning Management Systems (LMS), and blended learning, thereby expanding access and enriching both cognitive and spiritual learning experiences. However, this digital shift also introduces new risks related to child protection in online environments. National regulations mandate schools and higher education institutions, including PAK, to embed safeguarding principles into digital learning practices. Recent literature identifies three main research streams: the effectiveness of technology-enhanced learning, Christian ethics and digital spirituality, and faith-based digital literacy. Nonetheless, three research gaps remain: (1) limited integration of legal norms into technology-driven pedagogy, (2) absence of a safeguarding-by-design framework tailored for PAK, and (3) insufficient evaluation instruments to measure child protection outcomes in digital learning environments. This study aims to: (a) analyze the juridical implications of child protection regulations for the design, implementation, and evaluation of technology-based PAK strategies, (b) develop a “child-safe technology-based PAK framework” that integrates theological-pedagogical formation with regulatory compliance. The scientific contribution of this study lies in offering a PAK strategy that is not only pedagogically effective but also legally compliant, ethically grounded, and pastorally responsive thereby fostering a safe, inclusive, and child- centered learning ecosystem in the digital era.